Makna dan Pencarian Padanan Dalam Penerjemahan Lintas Budaya - Frans Sayogie (Buletin Al-Turas, 2005)
This article aims at conveying meaning and lexical-meaning in the cross-cultural translation of a given-cultural discourse from one language to another, for this case, English into Bahasa Indonesia or vice-versa. The meaning of a given word or set of words is best understood as the contribution that word or phrase can make tothe meaning or the whole sentence or linguistic and cultural utterance where that word or phrase occurs.